Interaction of monoclonal antibodies with mammalian choline acetyltransferase. - Crawford, G D (1982)
Monoclonal antibodies selective for rat brain choline acetyltransferase (acetyl-CoA: choline O-acetyltransferase, EC 2.3.1.6) were prepared by standard techniques. Five cell lines were isolated from spleen cell-SP/2 hybrids by repetitive cloning with a screening method that used the intrinsic activity of the enzyme. All cell lines secrete immunoglobulin of mouse subclass IgGl, and none inhibit the enzyme activity directly. The size of antibody-enzyme immune complexes formed with different pairs of the monoclonal antibodies was determined by gel filtration with HPLC. By comparing the elution position of choline acetyl-transferase activity after incubation with paired monoclonal antibodies, the spatial relationship of antibody binding domains relative to each other can be defined and classified as independent, mutually exclusive, or overlapping. Immune complexes in excess of Mr 600,000 were formed by some pairs of antibodies with the antigen, indicating independent binding domains on the enzyme. In one case, the paired antibodies formed an immune complex of only Mr 300,000, indicating that they bound in a mutually exclusive fashion. In most cases, pairs of antibodies reacted with the enzyme to give simultaneously both higher and lower Mr immune complexes. We conclude that all five antibodies bind to a relatively localized region of the enzyme surface. Antibodies were screened for usefulness as immunohistochemical markers of choline acetyltransferase-containing neurons by using the indirect immunoperoxidase method. One antibody intensely stains cell bodies of motor neurons and processes in a selective manner in the rat spinal cord and brain stem by using aldehyde-fixed tissue; the remaining antibodies do not react with fixed tissue.